Inventory Turnover Analysis Against Profitability at PT. Voksel Electric, Tbk - Suparno Suparno (Peneliti.net, 2022)
This study is to determine the effect of inventory turnover on profitability (net profit margin) at PT. Voksel Electric Tbk. This research is a study of two variables using quantitative descriptive research methods, namely the independent variable is inventory turnover and the dependent variable is profitability. The analysis technique used is simple linear regression analysis, correlation analysis, coefficient of determination analysis and t test. The results of the research analysis show that inventory turnover has an effect on profitability. This can be seen by the simple regression equation Y = 8.32 - 1.37 X with the value of correlation analysis (r) with the correlation obtained - 0.38 so that inventory turnover has a low effect on profitability. The results of the analysis of the coefficient of determination show that 14.44% of profitability is influenced by inventory turnover and 85.56% is influenced by other factors not examined. And the results of the t-test are Tcount < Ttable (-0.70 <3.182), then Ho is accepted and Ha is rejected because the results are not significant